Un essai de caractérisation du didactique - Lucile Vadcard (Recherches en Éducation)
This text proposes a characterization of what could constitute the essence of a didactic approach of educational issues. Based on the pioneer case of didactic of mathematics, we come back to some potentialities of this approach for vocational training. Doing so, we also formulate some remarks on the research domain of “didactique professionnelle” as it is presented in some of its founding texts. Finally, we propose some directions for further studies.